Multiple mini punch grafts for extensive ulcer: a case report - Wirohadidjojo, Yohanes Widodo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Multiple mini punch grafts is the placing of mini size of full thickness skins on to ulcer bed. Theyconsist of epidermal and dermal component composed with hair follicles and other skin appendiceswhere epidermal stem cells are located. The epidermal stem cells are the best source of epidermalcells in reconstruction of skin equivalent that is usually used for replacing classic split thicknessskin graft in recovering extensive ulcer. In this article, the application of multiple mini punchgrafts onto extensive ulcer is reported. A case of extensive ulcer was suffered by a 6-year-oldboy whose left foot is injured in a traffic accident. His toes had already been amputated bysurgeon but a classic skin graft failed to recover the ulcer. Multiple mini punch grafts had beenharvested from his inguinal and buttock skin and they were placed onto his ulcer. Pre and postmini punch grafting photographs were reviewed. After eight weeks, placed multiple mini punchtissues onto large ulcer reveals lateral extensions and more than 90% of epithelialization. Multiplemini punch grafts can be used as a method to cover large ulcer.Key words: mini punch grafts-large ulcer-epithelialization-epidermal-stem cells